Melayu: The Politics, Poetics and Paradoxes of Malayness by Maznah Mohamad and Syed Muhd Khairudin Aljunied (Editors), National University of Singapore Press, 2011, 392 pages - Zailan Moris (Kajian Malaysia, 2012)
Melayu: The Politics, Poetics and Paradoxes of Malayness is an interesting title for an edited volume of 12 essays discussing the subject of Malayness. In the preface, Maznah Mohamad and Syed Muhd Khairudin Aljunied, the two editors of this volume, state while the main aim of the book like many other books on Malay Studies is to examine the complex subject of Malay identity, it intends to distinguish itself by examining it "with new and wide-angled lenses." The "new and wide-angled lenses" involves both the widening of the scope of discourse by examining "neglected issues and social actors" such as the Orang Asli or aboriginal peoples of Malaysia, Peranakan Chinese and modern Filipinos; and also, the approach taken by the contributors.